Expansion/Facemask Treatment of an Adult Class III Malocclusion - Gregory W. Jackson; Neal D. Kravitz (Hindawi Limited, 2014)
The orthodontic treatment of class III malocclusion with a maxillary deficiency is often treated with maxillary protraction with or without expansion. Skeletal and dental changes have been documented which have combined for the protraction of the maxilla and the correction of the class III malocclusion. Concerning the ideal time to treat a developing class III malocclusion, studies have reported that, although early treatment may be the most effective, face mask therapy can provide a viable option for older children as well. But what about young adults? Can the skeletal and dental changes seen in expansion/facemask therapy in children and adolescents be demonstrated in this age group as well, possibly eliminating the need for orthodontic dental camouflage treatment or orthognathic surgery? A case report is presented of an adult class III malocclusion with a Class III skeletal pattern and maxillary retrusion. Treatment was with nonextraction, comprehensive edgewise mechanics with slow maxillary expansion with a bonded expander and protraction facemask.